Endothelial cell spreading on lipid bilayers with combined integrin and cadherin binding ligands. (15th August 2022) - Koçer, Gülistan; Albino, Inês M.C.; Verheijden, Mark L.; Jonkheijm, Pascal
Graphical abstract: Supported lipid bilayers (SLBs) offer great versatility in surface modification to construct cell-instructive biointerfaces. Co-insertion of integrin and N -Cadherin targeting ligands in SLBs and control over their molar ratios at the surface enables to tune the complexity of the cell-surface interface in a biomimetic way, to guide a tissue type specific (endothelial) cell response. Abstract: Endothelial cells play a central role in the vascular system, where their function is tightly regulated by both cell-extracellular matrix (e.g., via integrins) and cell–cell interactions (e.g., via cadherins). In this study, we incorporated cholesterol-modified integrin and N -cadherin peptide binding ligands in fluid supported lipid bilayers. Human umbilical vein endothelial cell adhesion, spreading and vinculin localization in these cells were dependent on ligand density. One composition led to observe a higher extent of cell spreading, where cells exhibited extensive lamellipodia formation and a qualitatively more distinct N -cadherin localization at the cell periphery, which is indicative of N -cadherin clustering and a mimic of cell–cell contact formation. The results can be used to reconstitute the endothelial-pericyte interface on biomedical devices and materials.